Detection of enhanced central mass-to-light ratios in low-mass early-type galaxies: Evidence for black holes? - Pechetti, R; Seth, A; Cappellari, M; McDermid, R; den Brok, M; Mieske, S; Strader, J (Institute of Physics, 2017)
We present dynamical measurements of the central mass-To-light ratio (M/L) of a sample of 27 low-mass early-Type galaxies. We consider all galaxies with 9.7 < log( < 10.5 in our analysis, selecting out galaxies with available high-resolution Hubble Space Telescope (HST) data, and eliminating galaxies with significant central color gradients or obvious dust features. We use the HST images to derive mass models for these galaxies and combine these with the central velocity dispersion values from data to obtain a central dynamical M/L estimate. These central dynamical are higher than dynamical derived at larger radii and stellar population estimates of the galaxy centers in ∼80% of galaxies, with a median enhancement of ∼14% and a statistical significance of 3.3σ. We show that the enhancement in the central M/L is best described either by the presence of black holes in these galaxies or by radial initial mass function variations. Assuming a black hole model, we derive black hole masses for the sample of galaxies. In two galaxies, NGC 4458 and NGC 4660, the data suggest significantly overmassive black holes, while in most others only upper limits are obtained. We also show that the level of M/L enhancements we see in these early-Type galaxy nuclei are consistent with the larger enhancements seen in ultracompact dwarf galaxies (UCDs), supporting the scenario where massive UCDs are created by stripping galaxies of these masses.